Implementasi Pembelajaran Berbasis CTL untuk Menumbuhkan Disiplin dan Tanggung Jawab Peserta Didik Kelas IV - Khikmah, Nurul; Hidayat, Nahara Ayunda; Widodo, SusiloTri; Ully, Ciek Sandrasyifa (Lembaga Yasin AlSys, 2025)
Although contextual learning (Contextual Teaching and Learning/CTL) has been widely discussed in previous research, studies that specifically examine its implementation in teaching the topic of making and implementing rules and its reinforcement of discipline and responsibility among elementary school students remain limited. This study aimed to describe the implementation of contextual learning in the topic of making and implementing rules and to analyze its influence on students’ understanding of the function of rules and the development of discipline and responsibility among fourth-grade elementary school students. The study employed a qualitative approach with a descriptive design, involving purposively selected fourth-grade students. Data were collected through classroom observation, group discussions, analysis of students’ worksheets (Lembar Kerja Peserta Didik, LKPD), and documentation of learning activities, and were then analyzed using thematic analysis techniques. The findings show that the implementation of contextual learning through activities such as watching videos, role-playing, analyzing illustrations, engaging in group discussions, and completing the LKPD “Aturan Kelas Kami” was effective in increasing student engagement, deepening their understanding of the purposes and functions of rules, and strengthening discipline and responsibility in school life. These findings contribute to the development of the contextual learning concept and broaden understanding of character education practices in elementary schools, while also underscoring the importance of learning approaches that connect instructional content with students’ real-life experiences in shaping positive character. The implications of this study include theoretical contributions to enriching CTL scholarship and practical implications for elementary school teachers in designing meaningful learning that is oriented toward strengthening students’ character.